Implementation Of Decision Support System In Determining The Location Of Public Wifi Installation Using The AHP (Analytical Hierarchy Process) Method - Wilfrida Handayani Panggabean; Miftahul Jannah (Putaka Timur Publisher, 2021)
In order to facilitate the community, the Deli Serdang Regency Government through the Deli Serdang Regency Communications and Information Office (Kominfo) has installed public wifi networks in public places that can be accessed for free by the public. in accordance with the amount provided by the Department of Communication and Information of Deli Serdang Regency because the budget is limited every year. Currently, choosing the right and strategic location in determining the Installation Location of Public Wifi is still done manually by conducting site surveys, so it takes a long time. For this reason, it is necessary to use technology in the field of decision support systems that provide information to help deal with existing problems. The method used is the AHP (Analytical Hierarchy Process) method. The criteria used are Distance from the Office of Communication and Informatics, Strategic Location, Economy, Visitors and, Place Convenience. The Decision Support System is then applied using PHP programming and MySQL database. It is hoped that this Decision Support System will make it easier for the Department of Communication and Information of Deli Serdang Regency to determine the Location of Public Wifi Installation.